Sagot :
a) 6x(3x-5)
18x²-30x
b) 3x(4x-3)+7(3x-4)
12x²-9x+21x-28
12x²+12x-28
c) (6x-5)(3x-4)
18x²-24x-15x+20
18x²-39x+20
factoriser :
d) 3x+6=3(x+2)
e) 4x²+6x=2x(2x+3)
f) (2x+3)(3x-2)+5(2x+3)=(2x+3)(3x-2+5)=(2x+3)(3x+3)
g) (5x+6)(2x-5)+(2x-5)(7x+2)=(2x-5)(5x+6+7x+2)=(2x-5)(12x+8)
H=(x+2)(x-3)+2x(x-3)
1) x²-3x+2x-6+2x²-6x
3x²-7x-6
2)(x-3)(x+2+2x)
(x-3)(3x+2)
3) x=2
(2+2)(2-3)+2(2)(2-3)
(4)(-1)+4(-1)
-4+(-4)
-4-4=-8
18x²-30x
b) 3x(4x-3)+7(3x-4)
12x²-9x+21x-28
12x²+12x-28
c) (6x-5)(3x-4)
18x²-24x-15x+20
18x²-39x+20
factoriser :
d) 3x+6=3(x+2)
e) 4x²+6x=2x(2x+3)
f) (2x+3)(3x-2)+5(2x+3)=(2x+3)(3x-2+5)=(2x+3)(3x+3)
g) (5x+6)(2x-5)+(2x-5)(7x+2)=(2x-5)(5x+6+7x+2)=(2x-5)(12x+8)
H=(x+2)(x-3)+2x(x-3)
1) x²-3x+2x-6+2x²-6x
3x²-7x-6
2)(x-3)(x+2+2x)
(x-3)(3x+2)
3) x=2
(2+2)(2-3)+2(2)(2-3)
(4)(-1)+4(-1)
-4+(-4)
-4-4=-8
Le x est la lettre, la multiplication sera marquée avec *.
Exercice 1:
A = 6x (3x-5) = 18x² - 30x
B = 3x (4x-3) + 7 (3x-4) = 12x² - 9x + 21x - 28 = 12x² + 12x - 28
C = (6x - 5) (3x - 4) = 18x² - 24x - 15x + 20 = 18x² - 39x + 20
Exercice 2:
D = 3x + 6 = 3 (x + 2)
E = 4x² + 6x = x (4x + 6) = 2x (2x + 3)
F = (2x + 3) (3x - 2) + 5 (2x + 3) = (2x + 3) (3x - 2 + 5) = (2x + 3) (3x + 3)
G = (5x + 6) (2x - 5) + (2x - 5) (7x + 2) = (2x - 5) (5x + 6 + 7x + 2) = (2x - 5) (12x + 8)
Exercice 3:
1. H = (x+2)(x-3) + 2x(x-3)
H= x² - 3x + 2x - 6 + 2x² - 6x
H= 3x² - 7x - 6
2. H= (x - 3) (x + 2 + 2x)
H= (x-3) (3x + 2)
3. x=2 donc on remplace x par le nombre 2.
= (2 + 2) (2 - 3) + 2*2 (2 - 3)
= (4*-1) + (4*-1)
= -4 + (-4)
= -8
Exercice 1:
A = 6x (3x-5) = 18x² - 30x
B = 3x (4x-3) + 7 (3x-4) = 12x² - 9x + 21x - 28 = 12x² + 12x - 28
C = (6x - 5) (3x - 4) = 18x² - 24x - 15x + 20 = 18x² - 39x + 20
Exercice 2:
D = 3x + 6 = 3 (x + 2)
E = 4x² + 6x = x (4x + 6) = 2x (2x + 3)
F = (2x + 3) (3x - 2) + 5 (2x + 3) = (2x + 3) (3x - 2 + 5) = (2x + 3) (3x + 3)
G = (5x + 6) (2x - 5) + (2x - 5) (7x + 2) = (2x - 5) (5x + 6 + 7x + 2) = (2x - 5) (12x + 8)
Exercice 3:
1. H = (x+2)(x-3) + 2x(x-3)
H= x² - 3x + 2x - 6 + 2x² - 6x
H= 3x² - 7x - 6
2. H= (x - 3) (x + 2 + 2x)
H= (x-3) (3x + 2)
3. x=2 donc on remplace x par le nombre 2.
= (2 + 2) (2 - 3) + 2*2 (2 - 3)
= (4*-1) + (4*-1)
= -4 + (-4)
= -8